1997
DOI: 10.1046/j.1365-2362.1997.1360683.x
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid inhibition of interferon activity in human lymphocytes: no evidence of oxidative stress

Abstract: Cholestasis and bile acids are two factors involved in resistance to interferon therapy in patients with chronic hepatitis C. As bile acids inhibit the biological activity of this cytokine in vitro and are capable of generating oxidative stress in hepatocytes, we investigated the potential involvement of such a mechanism in human lymphocytes. Thus, we evaluated (a) the effects of bile acids (0-200 mumol L-1) on lymphocyte reduced glutathione content and malondialdehyde production and (b) the ability of antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Thereby, bile acids have been shown to affect the function of cytokine-driven effector mechanisms of innate immunity, as well as the function of cells of innate and adaptive immunity, including monocytes, macrophages, NK cells, and T cells. Hence, bile acids affect intracellular signaling in response to type I IFNs or cytokines, such as IL-6, and subsequent gene expression in immune cells, such as NK cells or lymphocytes, as well as in epithelial cells, such as hepatocytes [11][12][13][14][15]. Moreover, bile acids alter the primary humoral response in human monocytes by inhibition of cell proliferation and exocytosis of Ig [16], and a variety of different reports indicates that they substantially impair macrophage functions, including phagocytic activity, as well as production of the cytokines TNF-␣ or IL-6, in response to inflammatory stimuli, such as LPS [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, bile acids have been shown to affect the function of cytokine-driven effector mechanisms of innate immunity, as well as the function of cells of innate and adaptive immunity, including monocytes, macrophages, NK cells, and T cells. Hence, bile acids affect intracellular signaling in response to type I IFNs or cytokines, such as IL-6, and subsequent gene expression in immune cells, such as NK cells or lymphocytes, as well as in epithelial cells, such as hepatocytes [11][12][13][14][15]. Moreover, bile acids alter the primary humoral response in human monocytes by inhibition of cell proliferation and exocytosis of Ig [16], and a variety of different reports indicates that they substantially impair macrophage functions, including phagocytic activity, as well as production of the cytokines TNF-␣ or IL-6, in response to inflammatory stimuli, such as LPS [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In earlier reports, bile acids have been shown to counteract IFN pathways in liver cells and natural killer cells (24)(25)(26). Podevin et al showed that bile acids inhibited IFN-induced 2Ј,5Ј oligoadenylate synthetase (OAS) activity in different hepatoma cell lines, including Huh-7 (26).…”
mentioning
confidence: 99%